Pediatric Case of Acute Epiglottitis due to Staphylococcus aureus - Shalabi, Marwan; Kilani, Muna; Shalabi, Reem; Al-Tamimi, Mohammad; Tarifi, Amjad (Jordan Medical Journal, 2025)
Epiglottitis is an inflammatory condition of the epiglottis and its nearby structures, and leads to fever, drooling, and sore throat. This potentially fatal disease can progress to airway obstruction and requires emergency intervention. Haemophilus influenza used to be the main causative agent for Epiglottitis. Here, we report a case of a 4-year-old patient with epiglottitis caused by Staphylococcus aureus demonstrated by a positive swab culture of the epiglottis.